Produktivitas Pekerjaan Struktur Pondasi Bore Pile pada Proyek Hotel X di Kota Lumajang - Handoyo, Tri; Ihsan, Daimil; Sucipto, Sucipto (Universitas Batanghari Jambi, 2026)
Construction productivity plays a crucial role in determining the success and efficiency of project implementation. In foundation works, particularly bored pile installations, productivity is often affected by various technical and environmental factors. This study focuses on analyzing the productivity of bored pile foundation work on the Hotel X project in Lumajang City and identifying the dominant factors that hinder performance. The research employed a mixed-method approach combining quantitative productivity analysis with qualitative field observations and interviews. Productivity data were calculated using the Unit Completed method, while statistical testing was conducted using SPSS software to determine the correlation between influencing variables such as materials, equipment, labor, environment, and management. The analysis revealed that for bored piles with diameters of 600 mm and 500 mm at depths ranging from 5 to 18 meters, the average productivity rate was 0.86 meters per hour per unit during a 37-day observation period (totaling 1,713 working hours). Material factors contributed most significantly to productivity losses, accounting for 39.66% of total lost work hours (165.53 hours out of 417.35 hours), followed by environmental, equipment, labor, and management factors. The findings demonstrate that inadequate material logistics and unstable soil conditions substantially reduce project efficiency. In conclusion, effective management of these key factors is essential to improve productivity performance in bored pile foundation work on construction projects.